ANALISIS PENERAPAN MEDIA WORDWALL PADA PEMBELAJARAN BAHASA ARAB DI SMPIT INSAN MULIA BOARDING SCHOOL PRINGSEWU - rahmawati, rima ajeng; Zakaria, Hamdal (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
One of the challenges that should not be ignored in learning Arabic is the lack of interest and motivation among students to study it. Wordwall is an example of an application that can be used as an engaging and interactive learning tool. This study aims to examine the implementation of wordwall media in Arabic language learning at SMPIT Insan Mulia Boarding School, Pringsewu. The researcher used a qualitative approach, and the data generated by this study are presented using a descriptive method. After analyzing the implementation of Wordwall media in Arabic language learning, the findings of this study show that Arabic language teachers demonstrate high and innovative competence in using Wordwall media. Several technical obstacles to implementing computer-based learning, such as power outages or application errors, were encountered. Both the teachers and the school administration are actively involved in training related to media and the development of technology-based teaching materials.